PERTIMBANGAN HUKUM PENGURANGAN PIDANA PENJARA DIBAWAH MINIMUM KHUSUS (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 2223 K/PID.SUS/2022) - Dhea Amanda Salwa; Vincentius Patria Setiawan (Verstek, 2023)
This article examines the legal considerations of judex juris towards reducing the prison term below the minimum number of narcotics crime cases contained in the Supreme Court Judgement Number 2223 K/Pid.Sus/2022. The purpose of this article is to find out the legal considerations of judex juris that improve the judex factie judgement with a reduction in the prison term in the Supreme Court Judgement No. 2223 K/Pid.Sus/2022. This research is a normative legal research with primary and secondary legal materials. Then the approach used is a case approach which is carried out by reviewing cases related to the issue at hand which has become a court decision that has permanent power. The technique of collecting legal materials using library research and the technique of analyzing legal materials is deduction with the syllogism method. Based on this research, the results were obtained that in the legal considerations of judex juris that correct the judex factie decision with a reduction in the prison period in the Supreme Court Judgement Number 2223 K / Pid.Sus / 2022 which uses SEMA Number 4 of 2010 juncto SEMA Number 3 of 2011 as the basis for the judge's consideration in passing the judgment is in accordance with the applicable legal rules.Keywords: Judex Juris judgement Improvement, Reduction of Criminal Period, Narcotics Crime.